1999
DOI: 10.1046/j.1471-4159.1999.0721843.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Neuroprotective Effects of Various Nitric Oxide Donor Compounds in Murine Mixed Cortical Cell Culture

Abstract: Nitric oxide (NO) has been implicated in both the pathogenesis of and protection from NMDA receptormediated neuronal injury. This apparent paradox has been attributed to alternate redox states of nitrogen monoxide, whereby, depending on the redox milieu, nitrogen monoxide can be neuroprotective via nitrosation chemistry or react with superoxide to form secondary toxic species. In our murine mixed cortical cell culture system, the NONOate-type NO donors diethylamine/NO complex, and spermine/NO complex sodium (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Indeed, whether NO is beneficial or detrimental is critically dependent on the concentration and duration of exposure as well as the cellular oxygen environment. [62][63][64][65][66][67]. Additionally, in the subset of astrocytes in which COX-2 and NOS-2 are co-expressed, a possible interplay may be functionally relevant as the enzymes have been shown to physically associate with one another in both in vitro and in vivo assays [68].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whether NO is beneficial or detrimental is critically dependent on the concentration and duration of exposure as well as the cellular oxygen environment. [62][63][64][65][66][67]. Additionally, in the subset of astrocytes in which COX-2 and NOS-2 are co-expressed, a possible interplay may be functionally relevant as the enzymes have been shown to physically associate with one another in both in vitro and in vivo assays [68].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrosative stress has a protective side where nitrosation of caspase 3 and 8 as well as PARP leads to protection against apoptosis 31-33 . Nitrosation and other oxidants closed NMDA channels preventing calcium influx [34][35][36][36][37][38] . Oxidative mechanisms such as nitration also have been shown to have biological signals of protection against apoptosis 39 .…”
Section: )mentioning
confidence: 99%
“…18 Yet a variety of exogenous NO donors have been shown to produce neuroprotective effects via nitrosation (NO+) chemistry. 19,20 In fact, recent in vitro and in vivo studies show that exogenous nitric oxide can act as a free radical scavenger and protect neurons (including dopaminergic neurons) from oxidative injury. 21,22 Although the molecular mechanisms of how exogenous NO donors contribute to neuroprotection are not completely understood, studies have shown that NO may confer neuroprotection by a variety of mechanisms.…”
mentioning
confidence: 99%